UPAYA MENGELOLA PSIKOSOMATIS DI TENGAH MASA PANDEMI COVID-19: SEBUAH STUDI KUALITATIF [THE EFFORTS TO MANAGE PSYCHOSOMATIC IN THE MIDST OF COVID-19 PANDEMIC: A QUALITATIVE STUDY] - Cahyaningrum, Dwi; Muslim, Aziz (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
The world was buzzing about the COVID-19 that altered the fabric of human life. Growing communities are psychosomatic by overactive anxiety, fear, and worry. The purpose of this study is to know and understand the efforts being made to manage excessive psychosomatic or anxiety in the midst of COVID-19 pandemic. This research uses qualitative methods with interviews techniques on subjects that are psychosomatic. The finding of this research is attempts on the subject's control of psychosomatic means by sifting the news, staying in good touch with the family, eating wholesome, nourishing food, thinking positive, and praying to god almighty to always be guarded and protected.